2020
DOI: 10.1186/s12935-020-01536-w
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a new gastric cancer cell line, XGC-1

Abstract: Background: To establish a primary human gastric cancer cell line. Methods: Fresh gastric cancer tissue samples were separated into a cell suspension, and DMEM/F12 medium containing 10% foetal bovine serum was used for primary culture and subculture. The morphology of the cells was observed under a light microscope, and the cell growth curve was plotted. A soft agar colony formation assay was used to detect the colony formation ability of the cell line. Immunohistochemical methods were used to detect cytokerat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Differing from the organoid culture method including inoculation in Matrigel (28)(29)(30), the establishment of gastric cancer organoids by suspension culture has the following advantages: i) In the absence of Matrigel, the cost of the organoid culture may be markedly reduced; ii) in terms of collection, passage, cryopreservation and drug screening, the model is simpler and more convenient to handle; and iii) without Matrigel in the culture process, the impact of the interaction between mouse-derived components and human-derived tumors is reduced. Regarding the acquisition of primary cells, based on the literature and previous cell culture experience (28)(29)(30)(31)(32), it is recommended that during the enzymatic digestion process, tissue digestion is diligently observed and duly terminated in time. In this regard, cell mass-like structures rather than single cells may markedly improve the success rate of cell lines or organoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differing from the organoid culture method including inoculation in Matrigel (28)(29)(30), the establishment of gastric cancer organoids by suspension culture has the following advantages: i) In the absence of Matrigel, the cost of the organoid culture may be markedly reduced; ii) in terms of collection, passage, cryopreservation and drug screening, the model is simpler and more convenient to handle; and iii) without Matrigel in the culture process, the impact of the interaction between mouse-derived components and human-derived tumors is reduced. Regarding the acquisition of primary cells, based on the literature and previous cell culture experience (28)(29)(30)(31)(32), it is recommended that during the enzymatic digestion process, tissue digestion is diligently observed and duly terminated in time. In this regard, cell mass-like structures rather than single cells may markedly improve the success rate of cell lines or organoids.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by our group have indicated how fibroblast contamination may be reduced during organoid culture (31,32). First, the epithelial layer should be sampled as much as possible when the tumor tissue is obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more cell models derived from human primary tumors with clear backgrounds are required for the study of CRC biology. Like other established cell lines, the novel PUMC1-CRC cells have some particular advantages, including: high phenotypic heterogeneity, decreased genetic shifts, ideal complements for tissue banks, new tools for the evaluation of anticancer agents, and endless sources for genetic or proteomic analysis 25 27 .…”
Section: Discussionmentioning
confidence: 99%
“…XGC‐1 had been successfully established from GC patients diagnosed with IGC by Ming classification 15 . The XGC‐1, AGS and NUGC2 cell lines (Cell Bank of the Chinese Academy of Sciences) were cultured in RPMI‐1640 (Thermo Scientific) supplemented with 10% fetal bovine serum (Thermo Scientific) at 37°C with 5% CO 2 and 90%–95% humidity.…”
Section: Methodsmentioning
confidence: 99%